Spatial personalities: a meta-analysis of consistent individual differences in spatial behavior. (13th January 2022) - Stuber, Erica F; Carlson, Ben S; Jesmer, Brett R
Abstract: Individual variation in behavior, particularly consistent among-individual differences (i.e., personality), has important ecological and evolutionary implications for population and community dynamics, trait divergence, and patterns of speciation. Nevertheless, individual variation in spatial behaviors, such as home range behavior, movement characteristics, or habitat use has yet to be incorporated into the concepts or methodologies of ecology and evolutionary biology. To evaluate evidence for the existence of consistent among-individual differences in spatial behavior – which we refer to as "spatial personality" – we performed a meta-analysis of 200 repeatability estimates of home range size, movement metrics, and habitat use. We found that the existence of spatial personality is a general phenomenon, with consistently high repeatability (r) across classes of spatial behavior (r = 0.67–0.82), taxa (r = 0.31–0.79), and time between repeated measurements (r = 0.54–0.74). These results suggest: 1) repeatable spatial behavior may either be a cause or consequence of the environment experienced and lead to spatial personalities that may limit the ability of individuals to behaviorally adapt to changing landscapes; 2) interactions between spatial phenotypes and environmental conditions could result in differential reproduction, survival, and dispersal, suggesting that among-individual variation may facilitate population-level adaptation; 3) spatial patterns of species' distributions and spatial population dynamics may be better understood by shifting from a mean field analytical approach towards methods that account for spatial personalities and their associated fitness and ecological dynamics. Abstract : The study of animal personality has focused on five main traits: exploration, boldness, activity, aggression, and sociality, but it is unclear whether animals display personality across additional behavioral domains. We investigated the generality of personality across spatial behaviors such as home-ranging, movement through space, and habitat use. We demonstrated that individuals consistently differed in these behaviors across taxa. The existence of spatial personality may influence wildlife distribution, abundance, interactions, and fitness, and thus effect the capacity for populations to adapt to environmental change.